2019
DOI: 10.1126/scisignal.aay4430
|View full text |Cite
|
Sign up to set email alerts
|

The ALK-1/SMAD/ATOH8 axis attenuates hypoxic responses and protects against the development of pulmonary arterial hypertension

Abstract: Dysregulated bone morphogenetic protein (BMP) signaling in endothelial cells (ECs) is implicated in vascular diseases such as pulmonary arterial hypertension (PAH). Here, we showed that the transcription factor ATOH8 was a direct target of SMAD1/5 and was induced in a manner dependent on BMP but independent of Notch, another critical signaling pathway in ECs. In zebrafish and mice, inactivation of Atoh8 did not cause an arteriovenous malformation–like phenotype, which may arise because of dysregulated Notch si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…Recently, we generated a constitutive Atoh8-KO mouse (Atoh8 LacZ(ex1) ) by replacing a large part of exon 1 with a LacZ-reporter cassette. 32 We confirmed that Atoh8 mRNA expression was absent in KO bone ( Fig. 2c, lower panel).…”
Section: Atoh8 Is Expressed In Osteoblasts In Adult Bonesupporting
confidence: 78%
See 4 more Smart Citations
“…Recently, we generated a constitutive Atoh8-KO mouse (Atoh8 LacZ(ex1) ) by replacing a large part of exon 1 with a LacZ-reporter cassette. 32 We confirmed that Atoh8 mRNA expression was absent in KO bone ( Fig. 2c, lower panel).…”
Section: Atoh8 Is Expressed In Osteoblasts In Adult Bonesupporting
confidence: 78%
“…1g); both regions are well conserved from zebrafish to humans. 32 In primary osteoblasts purified from newborn mouse calvariae or MC3T3-E1 osteoblasts, the anti-Smad1 antibody immunoprecipitated fragments of SBR1 and SBR2; while SBR2 signals were predominant, both SBRs were further enriched upon BMP-6 treatment ( Fig. 1h, i).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations